NeuroCOVID-19: a critical review - Guedes, Bruno Fukelmann (Arquivos de Neuro-Psiquiatria, 2022)
Background: The COVID-19 pandemic has challenged neurologists since its early days. Neurology consultation services were then overloaded by emergency department and intensive-care patients with acute neurological syndromes. These complications are better explained today, but the growing number of patients with reported longstanding neurological symptoms constitute an emerging, complex, and still poorly understood phenomenon. Objective: This review summarizes data on relevant neurological manifestations of acute SARS-CoV-2 infection and lasting post-infectious disease, also known as Long COVID. The complex history of Long COVID is examined to illustrate the upsides and challenges imposed by the active participation of patient communities in the production of medical knowledge. Methods: Narrative review. Results: Infection with the severe acute respiratory syndrome coronavirus 2 is associated with encephalopathy/delirium, cerebrovascular disease, headache, and peripheral nervous system involvement. Long COVID is a living concept jointly defined by patient communities, physicians and scientists, including neurologists. Conclusion:  Co-production of Long COVID knowledge between scientists and patients has initiated an era of patient-led research and evidence-based activism that acts as a two-edged sword - putting patient’s suffering in the spotlight, but with a tradeoff in methodological consistency.
Keywords: COVID-19; Cognitive Dysfunction; Patient Participation; Social Media